Two aberrations in the use or application of marginalism or microeconomic approach (Cultura Económica, 2019)
After establishing the principles of the microeconomic approach, which constitute a concrete way to contemplate and study the problems related to human behavior, decision making and current activities of people –in any field–, the work analyzes two defects or anomalies, converted into malpractice, both attributed or linked to the neoclassical model or mainstream of economic analysis, but not part of its nature or condition: the utilitarism interpretation of that approach and an excessive use, as an end in itself, of mathematics, with the aim of achieving a complete axiomatization of the model in the aspects or problems faced. Both deviations have served to justify the increasingly intervention of the economic system, which has also sought approval both in these utilitarian interpretations of the model or approach, as in its apparent mathematical-formal asepsis. But the development and evolution of this microeconomic approach achieved the professionalization of the economy as a scientific subject and as a professional or applied practice.
Keywords: marginalism; neoclassical economics; microeconomic approach; utilatiarianism; mathematization; interventionism